1973
DOI: 10.1172/jci107221
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Experimental Myocardial Infarct Size by Corticosteroid Administration

Abstract: A B S T R A C T The influence of the administration of pharmacologic doses of hydrocortisone on the extent and severity of acute myocardial ischemic injury and on subsequent necrosis after acute coronary occlusion was investigated in 28 dogs. In order to study acute myocardial injury, repeated epicardial electrocardiograms were recorded from 10 to 15 sites on the anterior surface of the left ventricle. Average ST segment elevation (ST) and the number of sites in which ST segment elevation exceeded 2 mV (NST), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(89 citation statements)
references
References 38 publications
2
86
0
1
Order By: Relevance
“…29 In previous studies, the effect of glucocorticoids during experimental myocardial infarction has not been uniformly consistent. In early studies, 30,31 protective effects were reported, as well as in more recent studies, 32 in which glucocorticoids were shown to attenuate myocardial apoptosis in neonatal pigs. Similar attenuation of apoptosis by glucocorticoids has been shown in neonatal rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 94%
“…29 In previous studies, the effect of glucocorticoids during experimental myocardial infarction has not been uniformly consistent. In early studies, 30,31 protective effects were reported, as well as in more recent studies, 32 in which glucocorticoids were shown to attenuate myocardial apoptosis in neonatal pigs. Similar attenuation of apoptosis by glucocorticoids has been shown in neonatal rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Corticosteroids inhibit endothelial cell activation and leukocyte-endothelial interaction, thereby exerting prominent, and very rapid, anti-inflammatory effects on the vasculature [12]. Steroid treatment improves survival of patients with acute myocardial infarction and protects the myocardium from experimental ischemic injury [13,14,15]. In ischemic stroke steroids can improve clinical outcome in a subset of patients with severe stroke and administration of high doses of corticosteroids substantially reduces tissue damage in experimental focal cerebral ischemia [16,17,18,19].…”
Section: Beneficial and Harmful Effects Of Corticosteroids In Acute Imentioning
confidence: 99%
“…Furthermore, in patients with active rheumatoid arthritis steroids rapidly inhibit leukocyte recruitment into inflamed joints [56]. In myocardial infarction and ischemic stroke, high-dose steroids cause a transient decrease in blood pressure and systemic vascular resistance accompanied by an increase in coronary and cerebral blood flow within minutes of administration [10,14,57].…”
Section: Rapid Nontranscriptional Effects Of Grmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Secondary ischemia in transplant organs or tissues often goes undetected in the initial stages, and becomes clinically apparent only when the chance of recovering the tissue is gone, despite review of anastomoses and monitoring vascular permeability. Tissue is then not perfused, leading to necrosis.…”
Section: Introductionmentioning
confidence: 99%